Rethinking policy options for export earnings - Jayant Parimal (South Centre, 2006)
Although the structure of International Trade has changed significantly in favour of manufactures, primary commodities remain extremely important for several developing as well as Least Developed Countries. A large number are still dependent on a limited basket of primary commodities for their exports. More than a billion people are still dependent on the production and export of primary commodities in these countries, especially in the Highly Indebted Poor Countries (HIPC), African, Caribbean and Pacific (ACP) countries and the Sub-Saharan African countries (SSA). Even today a major portion of these populations earns less than USD 1 a day. This paper is an endeavour to explore the Export Earning Instability experienced by the Commodity Dependent Developing Countries (CDDCs) originating from price volatility and its associated issues which "…constrain the ability of many developing countries to attain a path of stable and sustained growth and employment creation that could benefit all segments of their population and allow them to reach the [Millennium Development Goals] MDGs" (UNCTAD, 2005). It also attempts to suggest better policy options keeping in mind the lessons learnt from past efforts.
Keywords: 300; Exportpreis; Außenhandelsstruktur; Exportdiversifizierung; Wirkungsanalyse; Entwicklungsländer